Pengaruh Penyuluhan Kesehatan Terhadap Peningkatan Pengetahuan Tentang Pertolongan Tersedak Di Masyarakat - Misbah Nurjannah; Zulmah Astuti (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2021)
Choking is an emergency condition that must be given immediate help. Choking occurs due to airway obstruction caused by food or other foreign objects. This airway obstruction can result in death, because this blockage will cause interference with oxygenation. Most choking occurs at the age of under 5 years. This healtg education is carried out to provide understanding and knowledge of skill in the community. Purpose: This study was conducted to see the effect of health education on knowledge of choking management in the community. Methods: The type of research is quasi experimental. The research was conducted with health education online conducted, with amount 34 responden. Analysis data with SPSS IBM 25. Results: There is a difference in the value of knowledge on the pretest and posttest after health education with Î± (sig < 0.005). value pretest mean 45.20 and post test mean 74.78. Conclusion: Health education carried out is effective to increase knowledge about choking, even though health education is done online in pandemic covid-19.